Isolation and identification of Endophytic Fungi of Pandanus sp. and Alpinia sp. from Reserve Forest UiTM Negeri Sembilan / Nor’Aishah Hasan and Maizura Zaini - Hasan, Nor’Aishah; Zaini, Maizura (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Endophytes are an endosymbiont that colonize in plant without causing apparent disease. Medicinal plants have been proven as a host to endophytes fungi thus providing a rich reservoir of bioactive compounds. However, there is lack information available about medicinal plants associated endophytes. Therefore, in the present study, the presence of endophyticfungi inhabiting in leaves of Pandanus sp.and Alpinia sp.were isolated. Healthy and symptomless leavesof Pandanus sp. and Alpinia spweresurface sterilizedand used for the isolation of endophytes.Variation in the colonization frequency of endophyticfungi was observed in leaves of both species. Relatively, leaves of Pandanus sp. werefound to have greater colonization frequency (16.7%) as compared to leaves of Alpinia sp.(8.3%). A total of 3 fungal isolates were obtained and identified based on the morphology of fungal cultures and spores. Among them one unidentified isolate (P2)was group to Zygomycota phylum. Other two isolates were identified as species belong to Lentinus sp.(A1)and Colleotrichum sp.(P1). Finding in this study suggest the possible exploration of many suchbioactive compounds from this potential fungus.